Assessment of the role of the protected land in the preservation of the steppe in Southwest Algeria (Case of the Rogassa Region) - Benkaddour, Benyekhlef; Megharbil, Ahmed; Kechairi, Réda; Safir, Kassim Boudjelal (Biodiversity: Research and Conservation, 2022)
In the Algerian steppe (Rogassa) overgrazing led to the reduction of the surface of the pasture land and its biodiversity. The objective of this work was to highlight the importance of the protected land in maintaining biodiversity and preserving the degraded areas. A mixed sampling for the two different sites was adopted, where fifty floristic surveys were conducted using the Braun-Blanquet method. The analysis of the real biological spectrum of the unprotected land was marked by the strong dominance of the therophytes. However, in the protected land the chamaephytes dominated all of the biological types. The analysis of the biogeographic spectra revealed the reappearance of the endemic species (+3%). The Shannon Index was very important in this matter (2.43). The Student’s t-test of the biodiversity’s index showed a highly significant difference between the two sites. The ascending hierarchical classification revealed that the protected land is subdivided into four groups dominated respectively by: Macrochloa tenacissima, Lygeum spartum, Artemisia erba-alba and Hordeum murinum. The results of the Jaccard dissimilarity index indicated a strong difference of the order of 80% between the two areas.